Utilization of air wave to determine the quality of seismic refraction data in near surface geophysical survey - Masyhur, E.M.H. (European Association of Geoscientists and Engineers, EAGE, 2019)
This study has highlighted the reliability of air wave as a reference to determine the quality of seismic data especially for seismic refraction in near surface exploration. The velocities of the air waves recorded in the seismograph are 364 m/s and 370 m/s. These air wave velocities are within the range of speed of sounds in the air. The seismic data are in acceptance quality. Â© 2019 EAGE-GSM 2nd Asia Pacific Meeting on Near Surface Geoscience and Engineering.All right reserved.